In-vitro ovicidal activity of Azadirachta indica leaf extracts against Haemonchus contortus eggs - SINGH, D; SWARNKAR, C P; KHAN, P A; BHAGWAN, P S K (The Indian Journal of Animal Sciences, 2011)
Both organic and inorganic extracts from the leaves of Azadirachta indica were screened for their ovicidal property against Haemonchus contortus eggs. Only aqueous extract of A. indica leaves showed significant reduction in egg embryonation and egg hatching at a concentration of 1.25 mg/ml, suggesting presence of potent embryonicidal and ovicidal activity. Other type of extracts, viz. alcoholic, ether and chloroform failed to produce any appreciable effect on egg embryonation and hatching.Â